Food system photographic portrays: A necessary urban design agenda - Marat-Mendes, T.; d'Almeida, P. Bento; Borges, J (2nd International Conference on Food Design and Food Studies (EFOOD 2019), 2019)
Research suggests that design solutions are an influential factor in the sustainability performance of food sys-tems. Yet, such systems remain unexplored within architecture and urban design. We argue that Architectural Surveys of the 20th century encapsulate urban form solutions, which bear on food issues and therefore deserve further consideration. Our findings point out that identifying food concerns within such surveys would promote proposals of urban form design solutions, which are necessary to integrate contemporary urban planning com-pendiums, but also to promote further dialogues among those concerned for food and urban design.